PENGARUH KOMUNIKASI DAN KERJASAMA TIM TERHADAP KEPUASAN KERJA YANG BERDAMPAK PADA KINERJA KARYAWAN - Iryadana, Mohamad Razab; Sartika, Gita; Gunawan, Adriani; Tialonawarmi, Feny; Muslimat, Ade (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to determine the effect of communication and teamwork on job satisfaction which has an impact on employee performance at PT Agro Boga Utama in Bandung. The method used is explanatory research with a sample of 95 respondents. The analysis technique uses statistical analysis with regression testing, determination and hypothesis testing. The results of this research: Communication has a significant effect on job satisfaction of 35.3%, the hypothesis test obtained a significance of 0.000 <0.05. Teamwork has a significant effect on job satisfaction of 41.9%, the hypothesis test obtained a significance of 0.000 <0.05. Communication and teamwork simultaneously have a significant effect on job satisfaction of 49.7%, hypothesis testing obtained a significance of 0.000 < 0.05. Job satisfaction had a significant effect on employee performance of 30.3%, hypothesis testing obtained a significance of 0.000 < 0.05.